"ADA Library Conference 2014" Photo album - ADA University Library (ADA University, 2014)
ADA University hosted the 1st International Library and Information Science Conference with the theme of "Exploring Best Practices in Library and Information Science”. Photo album of ADA Library Conference 2014 provided for users to visualize Conference event.
Keywords: ADA University.; ADA University -- Conference materials.; ADA University -- Photo album